DEVELOPMENT OF A FUZZY-BASED TIDAL VOLUME ALGORITHM FOR PATIENTS WITH RESPIRATORY DISTRESS - Guler, Hasan; Ata, Fikret (Gazi Univ, Fac Engineering Architecture, 2014)
The purpose of the present study is to develop a fuzzy-based tidal volume algorithm for patients with respiratory distress. The standard of care when ventilating patients with the acute respiratory distress syndrome is to use a tidal volume of 6 ml/kg for ideal body weight. But, this tidal volume aim is frequently exceeded for many reasons, most typically related to physician discomfort with clinical parameters of inadequate oxygenation and ventilation. Thus, an algorithm based on fuzzy logic has been developed in Matlab to prevent deviation in tidal volume. The inputs of fuzzy were positive end-expiratory pressure (PEEP), plateau pressure (Pplt) and arterial oxygen saturation (SaO(2)) and the change of PEEP. Random clinical scenarios were generated via using Monte-Carlo simulation and Gaussian distribution methods. The student t-test for p <0.05 was used to compare the obtained results from simulations and clinicians' decision. It was found that there is no statistical discrepancy in the value of tidal volume. It can be said that this algorithm may prove useful as means of rationalizing and standardizing departures from desired 6 ml/kg tidal volume in any given patient.
Keywords: Fuzzy Logic; Mechanical Ventilation; Monte-Carlo Algorithm; Gaussian Distribution